Manajemen Stres Berbasis Teknik HeartMath untuk Mengurangi Stres dan Mengelola Emosi pada Caregiver Pasien Penyakit Kronis - Tiara Diah Sosialita; Hamidah Hamidah (Jurnal Ilmu Perilaku, 2020)
Abstract. This study was the continuance of the prior research of psychological intervention of patiens with type 2 diabetes mellitus. In this study, intervention was given to caregivers who caring of their family members in chronic illness. This consideration was chosen based on many feedbacks from community and health care personnels. This research was conducted as a solution to help caregivers of chronic illness deal with their stressful situation. Caregivers are required to care their family members optimally eventhough they are also vulnerable to stress. Based on this condition, the purpose of this research is to test the effectiveness of stress management to reduce stress level in 20 caregivers used experimental design, one group pretest-posttest design. Data collection used Perceived Stress Scale (PSS) questionnaire by Cohen. Data analysis used paired sample t-test with SPSS 20 showed that there was a significant difference of stress level between before and after stress management intervention. The result revealed that stress management is effective for reducing stress in caregivers. Keywords: Caregiver; chronic illness; stress management